The formation of reason - Bakhurst, David (Journal of philosophy of education book series, 2011)
"In The Formation of Reason, David Bakhurst expounds and defends a socio-historical account of the human mind. Inspired by the work of the influential philosopher John McDowell, Bakhurst maintains that the distinctive character of human psychological powers resides in our responsiveness to reasons, a capacity that develops in children as they are initiated into traditions of thinking and reasoning. In this process of formation (or Bildung), children enter 'the space of reasons' to become rational agents in self-conscious control of their thoughts and actions. In addition to exploring McDowell's ideas, Bakhurst draws on a variety of thinkers - including Davidson, Hacking, Ilyenkov, Strawson, Vygotsky, Wiggins, and Wittgenstein - to illuminate questions of personhood, identity, learning, rationality, and freedom. Offering an intellectually stimulating exploration of the conceptual foundations of the philosophy of education, The Formation of Reason breathes fresh life into a familiar but controversial idea: that the end of education is the cultivation of autonomy"--Provided by publisher.